The need for and use of modern pestetsidov feature in maize - Secun, M.; Snizhko, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The species composition of the most widespread weeds, pests and diseases in agrocenoses of maize in the zone of Western Polissia was studied. The effectiveness of timely implementation of cultural protection measures with the use of pesticides against the main pests ensures a grain yield of 9.39 t/ha.